Share this post on:

Ing to ETM (three), it may be obtained the following: T (t – (t)) (t – (t)) – e T (t)e(t) 0. (20)Determined by the inequality (six), the constraint circumstances of deception attack is often obtained as follows: T (t – (t)) F T F (t – (t)) – F T ( (t – (t))) F ( (t – (t))) 0. Combining the above Equations (18)21) Cefotetan (disodium) MedChemExpress yields the following: EV (t) two T (t)( IN P) T (t) T (t)(Q1 Q2) (t) – T (t – M)Q1 (t – M) T (t – T T T – M)Q2 ( t – M) 1 ( t) 1 1 ( t) two ( t) 2 2 ( t) A ( t)RA ( t) two B T ( t)RB ( t) T ( t – ( t)) ( t – ( t)) – e T ( t) e ( t) T (t – (t)) F T F (t – (t)) – F T ( (t – (t))) F ( (t – (t)))). (21)(22)T Define T (t) = [1 (t), T (t – (t)), T (t – M), e T (t), F T ( (t – (t)))], and then applying inequality (21) and also the Schur complement yields the following:EV (t) T (t) (t).(23)Based on the above evaluation, the condition 0 is enough to assure EV (t) 0. For that reason, we are able to conclude from Equations (15) and (23) that all UAVs inside the multi-UAV technique can track the trajectories from the leader though forming the designed formation under the proposed control scheme. This completes the proof. Theorem 1 gives a enough criterion of realizing TVFT. Depending on this, the design of control acquire K is Dihydrojasmonic acid Biological Activity presented in Theorem two. Theorem 2. Suppose that Assumptions 1 and 2 hold. For given event-triggering parameter i , the delay upper bound M , M , scalar 1 , two , 3 , the probability expectation of deceptionElectronics 2021, 10,9 ofattack , along with the matrix F, the formation tracking error method (14) is asymptotically stable ^ ^ ^ ^ ^ if there are actually constructive definite matrices P 0, Q1 0, Q2 0, R1 0, R2 0, i 0 ^ ^ (i = 1, two, . . . , N), X 0, Y 0 plus the matrices M, N in order that the following linear matrix inequalities hold: ^ 11 ^ 21 31 ^ ^ = ^ 41 ^ 51 ^ 61 ^ R1 ^ M exactly where ^ 11 ^ 21 ^ 31 ^ =41 ^ 51 ^ 61 ^^ -I 0 Z1 0 0 0 0 0Z2 0Z1 0, Z(24)^ R2 ^ 1 0, N ^ R^ 0, R(25)^^ 22 ^ 32 0 0 0^ 33 0 0 0^ 44 ^ 54 0^ ^ 55 0, ^ – 0 -^IT T ^ ^ ^ ^ ^ ^ ^ ^ ^ 11 =1 two , 1 = A1 X1 X1 A1 , 2 = Q1 Q2 – R1 – R2 , 11 11 11 11 T T T T ^ ^ ^ ^ ^ ^ ^ ^ 21 = – Y1 L1 – (Y1 W1) R1 M, 22 = -2R1 – M – M T ( L T I2)( L I2), ^ ^ ^ ^ ^ ^ ^ ^ 31 = – M, 32 = R1 M, 33 = -Q1 – R1 ,^ ^ ^ ^ ^ ^ ^ 41 =R2 N , 44 = -2R2 – N – N T , ^ ^ ^ ^ ^ ^ ^ ^ 51 = – N , 54 = R2 N , 55 = -Q2 – R2 , ^ ^ 61 = – Y T L T – Y T W T , 71 = Y T W T ,1 1 1 1 1^ 21 =FX^ ^ 0 , 31 = 1^ 2^ 2^ three ,^ ^ ^ 1 = M A1 X1 , three = M (W1 Y1), two = – M [ L1 Y1 W1 Y1 ], 31 31 31 1 two two three , ^ ^ ^ ^ ^ 41 = 41 41 0 0 0 41 41 ^ 1 = 41 ^3 M ( A1 X1), 41 ^ 1 51 ^ 1 61 0 0 0=0M^ (W1 Y1), 2 = -M [ L1 Y W1 Y1 ],^ 51 = 0 ^ 61 =^ 1 51 ^ 1^ ^ -1 , 1 = M (W1 Y1), 51 51 ^ ^ -1 , 1 = M (W1 Y1), 61A1 = Within a, X1 = IN X, Y1 = IN Y, W1 = W B, L1 = L B, ^ ^ Z1 = – 21 ( IN X) 2 R1 , Z2 = -22 ( IN X) 2 R2 .1^ ^ ^ ^ ^ ^ ^ ^ ^ ^ ^ Proof . Define X = P-1 , X = IN X, Q1 = X Q1 X, Q2 = X Q2 X, R1 = X R1 X, R2 = ^ ^ ^ ^ ^ ^ ^ ^ ^ ^ ^ X R2 X, M = X M X, N = X N X, = X X, Y = KX, then we can receive that- – ^ ^- ^ ^ ^- ^ ^ ^^ -R1 1 = – X R1 1 X, -R2 1 = – X R2 1 X, – I = – X I X.(26)Based on (R – P) R-1 (R – P) 0, where is usually a positive genuine quantity, R, P are constructive definite matrix, we’ve got the following:- PR-1 P -2P 2 R.(27)Electronics 2021, ten,10 ofCombining (26) and (27), we are able to receive the following: two ^ ^ ^- ^ ^ – X R1 1 X -21 X 1 R1 , two ^ ^ ^ ^- ^ – X R2 1 X -22 X two R2 , ^ ^^ ^ ^ – X I X -23 X two I.(28)Pre-multiplying and post-multiplying inequalities (15) and (16) with and , respectively, where = diag{ IN X, IN X, IN X, IN X, IN X, IN X,.

Share this post on:

Author: haoyuan2014